The Practice of Matemmba’ Arisang in Sidrap South Sulawesi and Its Perspective under Islamic Law - Sulkarnain Sulkarnain (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
The daily practice of Arisan has been carried out by all levels of society, each layer of society has its own tendency in holding the arisan. The phenomenon in Sidrap South Sulawesi is that making Arisan with unique games known as Mattemba Arisang’ meaning “Shooting Arisan”.This tudy aims to reveal the practice of debts and receivables in Mattemba' Arisang and elaborate it under of the perspective of Islamic economic law. This study was conducted at Sidrap of South Sulawesi. The informants of research were perpetrators of Practice of Matemmba Arisang. Data analysis used reduction, presentation, and verification. The results reveal that practice of Matemmba’ Arisang is conducetd using the contract of debt and receivable containing riba. gharar, and dzhulm. Therefore, According to a perspective of Islamic economic law on the implementation of Matemba' Arisang conducted by society in Pajalele Sidrap Regency has the receivable debt contract unsuitable with Islamic economic law